Central line-associated bloodstream infections caused by Staphylococcus aureus in cancer patients: Clinical outcome and management. (May 2014) - El Zakhem, Aline; Chaftari, Anne-Marie; Bahu, Ramez; El Helou, Gilbert; Shelburne, Samuel; Jiang, Ying; Hachem, Ray; Raad, Issam
Abstract Background. There are limited data regarding clinical presentation and management of Staphylococcus aureus central line- associated bloodstream infection (CLABSI) in immunocompromised cancer patients. Methods. In this review, we evaluated 299 patients with 304 episodes of S. aureus-CLABSI between 2005 and 2011. Findings. By multivariate analysis, the major predictors of complicated S. aureus-CLABSI were septic shock, catheter site inflammation, presence of peripherally inserted central catheter, anti-cancer chemotherapy within 10 days, and persistent bacteremia beyond 72 hours (P ≤ 0.02). A total of 67% of the cases were defined as complicated. In the subset of patients who were uncomplicated on presentation, patients receiving antimicrobials ≥ 14 days had similar rates of relapse, attributable mortality, and development of complications compared to those receiving shorter-course therapy. By competing risk analysis, removal of the catheter within 3 days of the onset of bacteremia was associated with a lower relapse rate at 90 days (P = 0.024). Interpretation. The majority of S. aureus-CLABSI in cancer patients are complicated and require prolonged course of antimicrobial treatment. Early removal of the catheter within the first 3 days is associated with better course. In patients with prompt removal of the catheter and no evidence of a complicated course, treatment beyond 2 weeks may not be necessary.